Telaah Kritis Evaluasi dan Implementasi Kurikulum Pembelajaran Bahasa Arab di Lingkungan Pesantren - Muhammad Tareh Aziz; Laili Mas Ulliyah Hasan; Muhammad Rido'i (DAARUS TSAQOFAH Jurnal Pendidikan Pascasarjana Universitas Qomaruddin, 2026)
Arabic language instruction has long been a hallmark of the historical excellence of Islamic boarding school education in Indonesia, although evaluation and curriculum implementation vary significantly across institutions. This paper aims to present a critical review of the evaluation and implementation of Arabic language curricula in Islamic boarding schools by summarizing a number of previous studies. The approach used is library research through thematic content analysis, with the Context, Input, Process, Product (CIPP) curriculum evaluation model used as a benchmark for comparing various cases. Three main conclusions emerge from this review. First, the diversity of Islamic boarding school Arabic language curricula is quite broad, ranging from Salafiyah Islamic boarding schools, whose curriculum relies on the authority of the kiai (Islamic scholars) and the tradition of the yellow books (kitab kuning), to Khalafiyah Islamic boarding schools, which implement the national curriculum in its entirety, to a combination of the two. Second, curriculum evaluation in various institutions still focuses primarily on product evaluation through learning achievement tests, while context and process evaluation are relatively understudied, resulting in a fragmented picture of curriculum success. Third, a gap has emerged between the direction of national policy, which requires communicative mastery of the four language skills, and the actual learning conditions, which are still closely tied to the grammar-translation approach, particularly in traditional Islamic boarding schools. This paper proposes a more responsive implementation-evaluation framework, one that combines the characteristics of the Islamic boarding school curriculum with the demands of national-scale communicative competency standards. The results of this review are expected to be useful as considerations for Islamic boarding school managers, policymakers, and future researchers in developing a more comprehensive and contextualized Arabic language curriculum evaluation system.